Biochemical and Structural Characterization of the Arabidopsis Bifunctional Enzyme Dethiobiotin Synthetase–Diaminopelargonic Acid Aminotransferase: Evidence for Substrate Channeling in Biotin Synthesis([C])([W]) - Cobessi, David (American Society of Plant Biologists, 2012)
Diaminopelargonic acid aminotransferase (DAPA-AT) and dethiobiotin synthetase (DTBS) catalyze the antepenultimate and the penultimate steps, respectively, of biotin synthesis. Whereas DAPA-AT and DTBS are encoded by distinct genes in bacteria, in biotin-synthesizing eukaryotes (plants and most fungi), both activities are carried out by a single enzyme encoded by a bifunctional gene originating from the fusion of prokaryotic monofunctional ancestor genes. In few angiosperms, including Arabidopsis thaliana, this chimeric gene (named BIO3-BIO1) also produces a bicistronic transcript potentially encoding separate monofunctional proteins that can be produced following an alternative splicing mechanism. The functional significance of the occurrence of a bifunctional enzyme in biotin synthesis pathway in eukaryotes and the relative implication of each of the potential enzyme forms (bifunctional versus monofunctional) in the plant biotin pathway are unknown. In this study, we demonstrate that the BIO3-BIO1 fusion protein is the sole protein form produced by the BIO3-BIO1 locus in Arabidopsis. The enzyme catalyzes both DAPA-AT and DTBS reactions in vitro and is targeted to mitochondria in vivo. Our biochemical and kinetic characterizations of the pure recombinant enzyme show that in the course of the reaction, the DAPA intermediate is directly transferred from the DAPA-AT active site to the DTBS active site. Analysis of several structures of the enzyme crystallized in complex with and without its ligands reveals key structural elements involved for acquisition of bifunctionality and brings, together with mutagenesis experiments, additional evidences for substrate channeling.